Use of Fillers for Optimal Formulation of Self-Compacting Concretes - Noufid, Abdelhamid; Belattar, Sougrati (Salehan Institute of Higher Education, 2018)
The objective of this study is to achieve an optimal formulation of self-compacting concrete using local materials from the country of Morocco, the use of this type of concrete remains very limited compared to a concrete vibrated in this country, due to lack mastery by companies. We will therefore try to study an optimal formulation that respects European standards and gives comparable results, even improved, to those of vibrated concrete, in order to be able to replace vibrated concrete with self-compacting concrete in construction sites. Thus, SCC mixtures containing amounts of fillers were examined, and with different Portland cement dosages: 350; 375 and 400 kg/m3. The method of formulation is made in accordance with French regulations. The results obtained were compared to these vibrated concrete counterparts containing the same cement dosages. Tests include compression, traction and flexion tests at 3, 7 and 28 days of age. Several studies have been carried out internationally, but at the national level, there is no study to this effect. The results obtained show that there is an improvement in the strength of concrete, in addition to the liquid appearance of concrete. It is this last aspect that characterizes the SCC, which allows it a flow in the areas inaccessible by the vibrator, thus saving time and performance of the structure to achieve.